Mediterranean coastline: the level of tourism satisfaction in the province of Valencia - Pimentel de Oliveira Santos, Danielle (2019)
The level of satisfaction in tourists and visitors of Canet d’en Berenguer, Cullera and Oliva, municipalities belonging to the province of Valencia in the Valencian Community, Spain, is assessed by means of a satisfaction survey, which was applied to 669 individuals. Also, in brief, the tourist offer of these tourist destinations is presented based on data from 2017, where there is a preference for beach tourist destinations, with a strong presence of national tourists who develop family activities. In addition, it is verified that the level of satisfaction with the destinations is high, with the intention of returning, even in cold periods. The incorporation of services is recommended throughout the year, to overcome the seasonal cycles of the destinations and promote a sustainable tourism.